Attainment's managing threatening confrontations [videorecording]. - White, Paul.; Reily, Rich.; Schultz, Jeff.; Attainment Co. (Verona, Wi. Attainment Co., 2004)
"Years of experience working with people who exhibit challenging behaviors helped Paul White create a five-stage framework for professionals to manage threatening confrontations. For frontline staff in the fields of developmental disabilities and mental illness who deal with potentially explosive situations"--Container.
"When to talk, when to listen, when to duck."--Container cover.
[Starring, Paul White ;director, Rich Reily, Jeff Schultz].
Keywords: Developmentally disabled -- Behavior modification; Mental illness -- Patients -- Behavior modification; Films for the hearing impaired